A review on the importance of miRNA-135 in human diseases - Kadkhoda, Sepideh; Eslami, Solat; Mahmud Hussen, Bashdar; Ghafouri-Fard, Soudeh (Frontiers in Genetics, 2022)
MicroRNA-135 (miR-135) is a microRNA which is involved in the pathoetiology of several neoplastic and non-neoplastic conditions. Both tumor suppressor and oncogenic roles have been reported for this miRNA. Studies in prostate, renal, gallbladder and nasopharyngeal cancers as well as glioma have shown down-regulation of miR-135 in cancerous tissues compared with controls. These studies have also shown the impact of miR-135 down-regulation on enhancement of cell proliferation and aggressive behavior. Meanwhile, miR-135 has been shown to be up-regulated in bladder, oral, colorectal and liver cancers. Studies in breast, gastric, lung and pancreatic cancers as well as head and neck squamous cell carcinoma have reported dual roles for miR-135. Dysregulation of miR-135 has also been noted in various non-neoplastic conditions such as Alzheimer's disease, atherosclerosis, depression, diabetes, Parkinson, pulmonary arterial hypertension, nephrotic syndrome, endometriosis, epilepsy and allergic conditions. In the current review, we summarize the role of miR-135 in the carcinogenesis as well as development of other disorders.